Improving the efficiency of virtual insulin teaching for patients admitted to hospital through the COVID-19 pandemic: a quality improvement initiative - Jeffery Tong; Tamara Spaic; Kristin K Clemens; Rebecca Meehan; Dane Iannicello; Raymond Li; Tisha Joy; Tsan-Hua Tung (BMJ Open Quality)
Background Throughout the COVID-19 pandemic, many areas of medicine transitioned to virtual care. For patients with diabetes admitted to hospital, this included diabetes education and insulin teaching. Shifting to a virtual model of insulin teaching created new challenges for inpatient certified diabetes educators (CDE).Objective We advanced a quality improvement project to improve the efficiency of safe and effective virtual insulin teaching throughout the COVID-19 pandemic. Our primary aim was to reduce the mean time between CDE referral to successful inpatient insulin teach by 0.5 days.Design, setting, participants We conducted this initiative at two large academic hospitals between April 2020 and September 2021. We included all admitted patients with diabetes who were referred to our CDE for inpatient insulin teaching and education.Intervention Alongside a multidisciplinary team of project stakeholders, we created and studied a CDE-led, virtual (video conference or telephone) insulin teaching programme. As tests of change, we added a streamlined method to deliver insulin pens to the ward for patient teaching, created a new electronic order set and included patient-care facilitators in the scheduling process.Main outcome and measures Our main outcome measure was the mean time between CDE referral and successful insulin teach-back. Our process measure was the percentage of successful insulin pen deliveries to the ward for teaching. As balance measures, we captured the percentage of patients with a successful insulin teach, the time between insulin teach and hospital discharge, and readmissions to hospital for diabetes-related complications.Results Our tests of change improved the efficiency of safe and effective virtual insulin teaching by 0.27 days. The virtual model appeared less efficient than usual in-person care.Conclusions In our centre, virtual insulin teaching supported patients admitted to hospital through the pandemic. Improving the administrative efficiency of virtual models and leveraging key stakeholders remain important for long-term sustainability.